2020
DOI: 10.21059/buletinpeternak.v44i3.47786
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Socio Economics Characteristics and Meat Self-Sufficiency Policy on Beef Cattle Farmer’s Income in Indonesia

Abstract: This study aimed to determine the influence of the implementation of the meat self-sufficiency policy on the cattle farmers’ income in Indonesia. This study used secondary data of Indonesian Family Life Survey (IFLS) that were collected in 2014. The IFLS are household data taken by survey at national level. This study used IFLS 5 data. The observed variables in this study included characteristics of farmer's household such as age, area of land cultivated, number of family members, education level, patterns int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Study conducted by Susanti et al, (2014) showed that the total cattle population in Indonesia decreased by 0.38 percent compared to 2018, and Aceh was one of four provinces in Indonesia that experienced a significant decrease in cattle population. A study conducted by Bawono et al, (2020) showed that factors such as cage management, feed, and animal health affect cattle productivity in Indonesia. The study also showed that there are still many farmers in Indonesia who have not implemented modern agricultural technology and good management systems.…”
Section: Location Quotient Analysis Of Cattle Population In Aceh Prov...mentioning
confidence: 99%
“…Study conducted by Susanti et al, (2014) showed that the total cattle population in Indonesia decreased by 0.38 percent compared to 2018, and Aceh was one of four provinces in Indonesia that experienced a significant decrease in cattle population. A study conducted by Bawono et al, (2020) showed that factors such as cage management, feed, and animal health affect cattle productivity in Indonesia. The study also showed that there are still many farmers in Indonesia who have not implemented modern agricultural technology and good management systems.…”
Section: Location Quotient Analysis Of Cattle Population In Aceh Prov...mentioning
confidence: 99%
“…The limited availability of superior breeding cattle, the low quality and availability of feed, suboptimal reproductive efficiency, and disease outbreaks are technical challenges requiring attention [8]. Furthermore, according to Bawono et al [9], the availability of land for carrying capacity on livestock business should pay more attention to achieve meat self-sufficiency. If this disparity continues longterm, it may threaten domestic food stability.…”
Section: Introductionmentioning
confidence: 99%